3(5x+13)=2(x+39)

Simple and best practice solution for 3(5x+13)=2(x+39) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5x+13)=2(x+39) equation:



3(5x+13)=2(x+39)
We move all terms to the left:
3(5x+13)-(2(x+39))=0
We multiply parentheses
15x-(2(x+39))+39=0
We calculate terms in parentheses: -(2(x+39)), so:
2(x+39)
We multiply parentheses
2x+78
Back to the equation:
-(2x+78)
We get rid of parentheses
15x-2x-78+39=0
We add all the numbers together, and all the variables
13x-39=0
We move all terms containing x to the left, all other terms to the right
13x=39
x=39/13
x=3

See similar equations:

| 11/12x+8=x | | 4(x+8)+4(x+16)=8 | | x^2-16x+41=0 | | x/3+25=67 | | 2x/2=28 | | 2^2y×5^(y-1)=8^y×5^2y | | x²-20x-40=0 | | -2x+-12-1=-9 | | 3(x+5)/4(x-2)=0 | | 4x+150/2=100 | | 7x+2=30-15 | | 5x+90=1000 | | 9x+2-15=175 | | 7x=8=30 | | X×2×y=168 | | (5x+7)/(-5x-7)=0 | | 2x+20/5=10 | | (x+9)^2=21 | | 4x+50/2=100 | | 64^2x=0 | | n÷2.5-7=-82 | | ((30x+42)/8)(x+5)/(5x^2-3x-14)=0 | | 3/8=w+3 | | ((30x+42)/8)((x+5)/(5x^2-3x-14))=0 | | 3(x-x^2)-4=4x^2+1 | | 6x+8=34+18 | | 4x^2-4x+4x^2-4x-48=0 | | 2.5-x/3.2=5/2 | | 15x^2-48x+108=0 | | Z=12-x | | 2x+15=-5x-13 | | 18(-x-2)-4(-8+3x)=-14 |

Equations solver categories